PENERAPAN STANDAR GRI SEBAGAI PANDUAN PENYUSUNAN LAPORAN KEBERLANJUTAN TAHUN 2020 PERUSAHAAN SEKTOR BARANG KONSUMEN PRIMER DAN NON-PRIMER DI BURSA EFEK INDONESIA - Breliastiti , Ririn (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2021)
Social Responsibility is a commitment to participate in sustainable economic development in order to improve the quality of life and the environment that is beneficial, both for the company itself, the local community, and society in general. PT Indofood Sukses Makmur Tbk (represented by IndoAgri), PT Unilever Indonesia and PT ACE Hardware Indonesia Tbk have used approaches and options in preparing the Sustainability Report, and have determined the basis for determining material topics. The sustainability strategy has been well explained by the three companies and identified in line with the SDGs. The three companies have made disclosures on both standards, namely universal standards and topic-specific standards. PT Unilever Indonesia Tbk uses independent assurance services, but PT Indofood Sukses Makmur Tbk (IndoAgri) and PT ACE Hardware Indonesia Tbk do not use independent assurance services. Keywords: Sustainability Report, GRI, IDX